Experimental and Clinical Studies on the Effects of Natural Products on Noxious Agents-Induced Lung Disorders, a Review - Saadat, Saeideh; Beigoli, Sima; Khazdair, Mohammad Reza; Amin, Fatemeh; Boskabady, Mohammad Hossein (Frontiers in Nutrition, 2022)
The harmful effect of various noxious agents (NA) is well shown and there are reports regarding the induction of various lung disorders due to exposure to these agents both in the animal and human studies. In addition, various studies have shown the effect of natural products (NP) on NA induced lung disorders. Therefore, the effects of various NP including medicinal plants and their derivatives on lung injury induced by NA were review in this article. The improving effects of various NP including medicinal plants such as Aloe vera, Anemarrhena asphodeloides, Avena sativa, Crocus sativus, Curcuma longa, Dioscorea batatas, Glycyrrhiza glabra, Gentiana veitchiorum, Gentiopicroside, Houttuynia cordata, Hibiscus sabdariffa, Hochu-ekki-to, Hippophae rhamnoides, Juglans regia, Melanocarpa fruit juice, Mikania glomerata , Mikania laevigata, Moringa oleifera, Myrtus communis L., Lamiaceae, Myrtle, Mosla scabra leaves, Nectandra leucantha, Nigella sativa, Origanum vulgare L , Pulicaria petiolaris, Paulownia tomentosa, Pomegranate seeds oil, Raphanus sativus L. var niger, Rosa canina, Schizonepeta tenuifolia,Thymus vulgaris, Taraxacum mongolicum, Tribulus Terrestris, Telfairia occidentalis, Taraxacum officinale, TADIOS, Xuebijing, Viola yedoensis, Zataria multiflora, Zingiber officinale , Yin-Chiao-San and their derivatives on lung injury induced by NA were shown by their effects on lung inflammatory cells and mediators, oxidative stress markers, immune responses and pathological changes in experimental studies. Some clinical studies also showed the effect of NP on respiratory symptoms, pulmonary function tests (PFT) and inflammatory markers. Therefore, the results of this review article showed the possible therapeutic effects of various NP on NA-induced lung disorders by amelioration of various features of lung injury. However, further clinical studies needed to support the therapeutic effect of NP on NA-induced lung disorders for clinical practice purpose.